Lies and crimes: Dark Triad, misconduct, and high-stakes deception. (January 2016) - Azizli, Nicole; Atkinson, Breanna E.; Baughman, Holly M.; Chin, Kristi; Vernon, Philip A.; Harris, Elizabeth; Veselka, Livia
Abstract: The goal of the present investigation was to assess whether the Dark Triad traits (Machiavellianism, narcissism, psychopathy) add significantly to the prediction of misconduct and the propensity to engage in high-stakes deception. Self-report scores were collected (n = 464) via the Short-D3 assessing the Dark Triad traits, the Comprehensive Misconduct Inventory measuring misconduct, and the Propensity to Lie Questionnaire investigating lying tendencies. Significant correlations were observed between nearly all variables, but in a multiple regression only psychopathy added significantly to the prediction of the misconduct factors. Further, only Machiavellianism was a significant predictor of high-stakes deception over and above the other predictors in the model. Highlights: Dark Triad correlated with most dimensions of misconduct behavior. Dark Triad correlated with most dimensions of high-stakes deception. Psychopathy added significantly to the prediction of misconduct factors. Machiavellianism added significantly to the prediction of high-stakes deception factors.